2012
DOI: 10.1080/07399332.2012.655392
|View full text |Cite
|
Sign up to set email alerts
|

Ugandan Men's Attitudes Toward Their Partner's Participation in Antenatal HIV Testing

Abstract: Several authors have shown that women's uptake of antenatal HIV testing is influenced by fear of their partners' reactions. We conducted a qualitative study with 40 Ugandan men to examine their attitudes toward their partners' participation in antenatal HIV testing. Most men believed women should consult their husbands prior to HIV testing to avoid negative consequences and facilitate disclosure. When women tested during routine antenatal care, however, the need to obtain permission was considered less importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Male involvement in PMTCT is in keeping with traditional values that confers authority to men in most households. This finding remains consistent with a study in Uganda, where society expects men to have authority over women and that HIV testing needed to be preceded by consent from a partner [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Male involvement in PMTCT is in keeping with traditional values that confers authority to men in most households. This finding remains consistent with a study in Uganda, where society expects men to have authority over women and that HIV testing needed to be preceded by consent from a partner [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study reported that MI in PMTCT creates an opportunity for individual men and couple HIV testing. This finding is in agreement with studies in Uganda, Kenya, and the Democratic Republic of Congo, where men felt that it promotes HIV Testing and Counselling (HTC) [ 36 ]¿[ 38 ] although some men within the Kenyan study viewed HIV testing as a deterrent for MI [ 37 ]. Human immunodeficiency testing is low in men even after accounting for HIV testing in women following PMTCT testing [ 39 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…35,36 Additionally, fear of male partners' response as well as the fear of potential stigma and violence faced at the hands of community and family members served as a deterrent. 37,38 The current study revealed examples of HIV positive individuals being isolated from their family and friends as a result of their status. Participants also discussed the role of stigmatization and fear of being treated as an outcast by the community as barriers to knowing one's status.…”
Section: Discussionmentioning
confidence: 74%
“…Several exploratory and feasibility studies have investigated the potential for male involvement in HIV testing and prevention [7, 15, 16], sexual and reproductive health [17, 18] and safe motherhood initiatives [18–24]. The only exploratory study identified related to newborn care targeted preterm care [25].…”
Section: Introductionmentioning
confidence: 99%